Poderia me ajuadar nessa questão ∫ (t + √t + 3√t + 4√t + 5√t)dt
Soluções para a tarefa
Respondido por
2
Resposta:
∫ (t + √t + 3√t + 4√t + 5√t) dt
∫ t + 13*t^(1/2) dt
=t²/2 + 13 * t^(3/2) /(3/2) + constante
=t²/2 +13*2/3 *t^(3/2) + constante
=t²/2 + 26/3√t³ +constante
=t²/2 + (26/3)* t√t +constante
lnard:
vlw,muito obrigado
Perguntas interessantes
Matemática,
10 meses atrás
Matemática,
10 meses atrás
Sociologia,
10 meses atrás
Matemática,
1 ano atrás
Sociologia,
1 ano atrás
Saúde,
1 ano atrás
Saúde,
1 ano atrás